A study of the trends and patterns of job advertising in special libraries - Bennett, Clark Raymond G. 1969-
"The purpose of this study is to know the trends and patterns used in special libraries to advertise jobs. It specifically seeks to find out the occupational composition of vacancies and the instrumentalities that are most frequently employed to advertise job offerings as a job vacancy measure in the area of Pasig, Metro Manila. It also tries to determine the frequency that each mode is being used and, thus, point out which advertising modes are trendy comparing them according to length of utility and frequency in engaging in the service of the applicant. The sample consists of fifteen special libraries. The respondents are library personnel of the different special libraries in Ortigas Complex of Pasig, Metro Manila. The descriptive method is used in this study. A set of questionnaires is used for the personnel in charge of hiring . The questionnaire is the primary tool for data gathering supplemented by interviews. Secondary sources are consulted such as the records of the Human Resources Development Office particularly in hiring library personnel. Frequency and percentage are used for the statistical tests. The survey finding indicated that: (1)job openings advertised by special libraries as a job measure indicates a pattern of unfilled demand for labor. The majority of vacancies that occur pertain to professional, technical and related works. Furthermore, the demand for labor increases with the passage of time; (2) The frequency that information channels are used for advertising indicates trends of search modes utilized for information. Informal advertisement channels are used more extensively than formal channels; (3) The different information networks of job advertising are utilized to a greater extent for educated workers than for semi-skilled or unskilled workers. Further areas of research were suggested which are not within the scope of the study. Likewise recommendations were given to employers who incur the cost of advertisement, so they could utilize the appropriate information channels depending on the quality of workers they wish to hire, to the job seekers so they may gain the benefits of learning about their potential employers, and to the employment service agencies, so they may provide a wide, if not perfect knowledge, of all the various alternatives in their task of matching men and jobs. "